An Analysis of Indonesian – English Code Mixing Used in Youtube by Indonesian Beauty Vlogger Titan Tyra - Sari, Ni Putu Nandya Yunita; Ayomi, Putu Nur; Jayantini, I GA Sri R. (Journal of Language and Applied Linguistics, 2023)
This study concerned Indonesian – English code-mixing in Titan Tyra’s YouTube channel. This thesis aims (1) To find out the types of code-mixing used by Titan Tyra in YouTube channel. (2) To find out the reasons why she used code-mixing on her YouTube channel. The informal method was used to give clear description about the data collection this study uses the theory proposed by Hoffman (1991) to analyze the types and the reasons of the code-mixing. The results of this study show that all types and reasons of code-mixing as proposed by Hoffman (1991) were found: the types are Intra-sentential code-mixing, Intra-lexical code-mixing, and involving a change of pronunciation. The reasons of using code-mixing are talking about a particular topic, interjection, repetition used for clarification, being emphatic about something, and expressing group identity.